2004
DOI: 10.1017/s0021932003006151
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Demographic Determinants of Regional Differences in the Prevalence of Obesity

Abstract: Differences in the prevalence of obesity between adjacent regions are quite common, but usually unexplained. This study examined whether birth place, selective migration, intelligence or education – which are both inversely and possibly causally related to obesity – are determinants of such differences. This population-based case-control study (case-cohort design) took place in the greater Copenhagen area (region 1) and surrounding provincial areas of Zealand (region 2), Denmark. A total of 2948 men with a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…By contrast, in less-developed countries, primarily in Central and Eastern Europe, low level of schooling is found to be associated with low risk of obesity (11,13) , which may reflect limited access to food and necessity for hard physical labour in individuals of low social position (10) . Our findings of a higher likelihood of obesity in men and women living in rural areas or areas outside the capital centre are also consistent with findings from other studies (16)(17)(18)28) . A study from Finland examining causes of BMI differences in relation to urbanization found that a clustering of individuals with a similar social status and an equal BMI status could be explained by both social selection (individuals of similar social position and with similar body composition choose to live in the same areas) and social causation (individuals who live in the same areas are affected by the local culture, e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, in less-developed countries, primarily in Central and Eastern Europe, low level of schooling is found to be associated with low risk of obesity (11,13) , which may reflect limited access to food and necessity for hard physical labour in individuals of low social position (10) . Our findings of a higher likelihood of obesity in men and women living in rural areas or areas outside the capital centre are also consistent with findings from other studies (16)(17)(18)28) . A study from Finland examining causes of BMI differences in relation to urbanization found that a clustering of individuals with a similar social status and an equal BMI status could be explained by both social selection (individuals of similar social position and with similar body composition choose to live in the same areas) and social causation (individuals who live in the same areas are affected by the local culture, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…A social gradient has been found in the prevalence of obesity: in most Western countries, individuals with lowest social position have the highest prevalence of obesity (11)(12)(13)(14) . Obesity is found to be associated with different measures of sociodemographic and socio-economic status, such as low level of schooling (11,12,14,15) , living in rural areas (16)(17)(18) , low household income (12,14) and unemployment (14,19) . The influence of social factors on obesity has been found to differ between sexes; more social factors have been found to be associated with obesity in women than in men and the associations between obesity and social factors have been found to be stronger and more consistent throughout the literature in women than in men (2,5,11,12,20) .…”
mentioning
confidence: 99%
“…However, the factors that contribute to creating this gap remain unclear. Finally, we have identified two studies that, in a similar vein to ours, examine within-country differences in obesity: between two regions in Denmark (Halkjaer and Sørensen, 2004) and across Spanish regions (Gutierrez-Fisac et al, 1999). The evidence drawn from these studies suggests that differences are mainly attributable to educational level and intelligence test scores.…”
Section: Italy Spainsupporting
confidence: 55%
“…There have been other studies that have examined the relation between obesity and various aspects of cognitive function [28][29][30][31][32][33] ; however, these studies were unable to distinguish whether the reduced intellectual performance could be ascribed to the obesity or if it was due to the association of obesity with lower socioeconomic status and lower educational level. Indeed, one recent report found that the differences in test scores between overweight and normal-weight children could be explained by differences in socioeconomic variables.…”
Section: Discussionmentioning
confidence: 99%